Drill-bit upper limit temperature calculation when drilling bones in orthopedic surgery - Tony Boiadjiev; George Boiadjiev; Ivan Chavdarov; Kamen Delchev; Rumen Kastelov (Biotechnology & Biotechnological Equipment)
The orthopedic manipulation of bone drilling is performed during the osteosynthesis of bone fractures. It is characterized by a set of input and output parameters. The temperature in the tool-bone interaction zone is one of the most important output parameters of the drilling process. The increase in temperature above a certain threshold causes thermal osteonecrosis of bone cells and all the resulting negative consequences. This work presents a way of drill-bit upper limit temperature calculation during robotized bone drilling process. The temperature estimation and temperature calculation methodology is based on the energy conversion in the bone-robot system, preserving the overall energy balance according to the universal energy conservation law. The bone drilling is performed by using of robot ODRO. Fresh porcine femur bones are used as specimens in the experiments which validate the theoretical results. The real time temperature data during drilling are obtained using a non-contact temperature sensor. A computational approach is developed for estimating the temperature in the drilling zone on the base of the obtained data.The temperature estimation data can be used to control of the cutting condition during a robotic bone drilling process in order to obtain an optimal outcome.